Students’ Learning Strategies to Increase Their English Reading Interest - Perti, Desy Puspasari; Muhayyang, Maemuna; G, Hasriani (Program Studi Pendidikan Bahasa Inggris FBS UNM, 2025)
This research focused on identifying the learning strategies of eighth-grade students at SMPN 18 Makassar to increase their English reading interest. This research used a descriptive qualitative method to achieve the research objective. The data was collected through interviews. The subject of this study was 7 students of grade VIII SMPN 18 Makassar, academic year 2023/2024, and selected using a simple random sampling technique. The findings revealed that the students applied cognitive, metacognitive, and socio-affective strategies in improving their reading interest. Cognitive strategies help students understand and remember information better by summarizing the text. Metacognitive strategies such as planning, monitoring, and evaluating help students to manage their learning process, which makes reading more purposeful. Socio-affective strategies involve social interaction and emotional support, like interacting with friends or teachers, and self-reward makes reading more enjoyable. Therefore, it is essential to incorporate these strategies into educational practices to make reading more effective and enjoyable for students.